Synthesis and physical property studies of cyclometalated Pt(II) and Pd(II) complexes with tridentate ligands containing pyrazole and pyridine groups. (15th November 2020) - Kumarasamy, Keerthika; Devendhiran, Tamiloli; Lin, Mei-Ching; Chiu, Chi-Wen
Graphical abstract: New cyclometalated palladium(II) and platinum(II) complexes incorporating tridentate ligands were synthesized. The expected complexes were attained in a reasonable quantity. The structures of ligand 7 and complex 11 were solved by single-crystal X-ray diffraction analysis. Photophysical studies were carried out for the complexes. Highlights: The synthesis of cyclometalated complexes is reported. 2, 6-Dibromopyridine was used as the starting material. Substituted tridentate ligands were synthesized and characterized. Cyclometalated Pt(II) and Pd(II) complexes were synthesized and characterized. Physical property studies of the obtained compounds were carried out. Abstract: Novel substituted tridentate ligands, which contains a series of pyrazole and pyridine groups as donors, and their cyclometalated complexes have been successfully synthesized. The ligands and complexes were completely characterized by a variety of techniques, such as 1 H NMR, UV–Vis, FT-IR, mass spectrometry and elemental analysis. Meanwhile, the single crystal structures of ligand 7 and complex 11 were determined by X-ray crystallography. For ligand 7, due to the effect of delocalization, the C(6)-C(7) bond length in the pyrazole ring is 0.05 Å shorter than a normal C-C bond. After coordinating with the metal centre, the configuration was limited by the coordination sphere, so the bond lengths and bond angles of complex 11 are different from those of ligand 7 . Through photoluminescence in acetonitrile solution at ambient temperature, two emission bands have been found between 500 and 600 nm for complexes 9 and 10 . Moreover, there are several absorbing bands respectively located at 240 to 250 nm and 300 to 310 nm for ligands 7 and 8 (π(L) → π*(L) and n → π*(L)). A red-shift was observed in the UV spectra, on comparing the complexes with electron-donating and electron-withdrawing groups on the ligand, which is due to the electronic effect of the substituent. One absorbing band is also found at 375 to 425 nm for complexes 9 and 10, and this band is attributed to a MLCT (dπ(Pt) → π*(L)).